Analysis of Teachers' Readiness in the Implementation of the Merdeka Belajar Curriculum - Aulia, Shopwatul; Sinta Arni; Intan Nur'aini; Oktia Qonita; Abdurrahmansyah (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This research is motivated by the challenges in the implementation of the Merdeka Belajar Curriculum, which requires teachers' readiness in cognitive, attitude, and behavioral aspects. The purpose of this study is to analyze teachers' understanding of the curriculum concept, practices in designing learning tools, implementation of formative and summative assessments, as well as supporting and inhibiting factors at SDN 08 Palembang. A qualitative descriptive research design was used with semi-structured interview instruments. The population consisted of seven teachers, who were selected as a total sample. Thematic data analysis techniques were applied through data familiarization, coding, theme determination, and interpretation. The results indicate that teachers have high enthusiasm and implement differentiated learning and creative assessments; however, technical understanding of ATP (Annual Teaching Plan) and assessment rubrics still varies. Supporting factors include the principal’s support, independent PMM training, and MGMP collaboration, while challenges involve limited internet access, administrative burdens, and training materials that are not contextual. The conclusion emphasizes the need for field mentoring, improvement of teachers' digital literacy, adaptation of training materials based on local context, and formal recognition to maintain motivation.